Relationship Between Total Quality Management Practice and Organizational Performance: A Conceptual Model Based on Iraq Manufacturing Industries - Al-Rawi, Najdat Hameed; Mohammad, Musli; Ahmad, Md Fauzi (International Journal of Integrated Engineering, 2020)
Many organizations use various organizational improvement initiatives such as ISO 9001, Total Quality Management (TQM) and Innovation Management as strategies to be competitive in their market segments. Despite the global acceptance of the TQM concept by manufacturing and service organizations, Iraqi manufacturing organizations are still at the primary stage of the TQM journey. This paper attempts to discuss the relationships between TQM implementation and organizational performance. It also argues the importance of innovation and ISO 9001 as mediators between the application of TQM and organizational results. The related literature was reviewed prior to the development of a framework which included TQM practice, ISO 9001, innovation and organizational performance. It is expected that ISO9001 and innovation would help the practice of TQM in enhancing organizational performance. Data collection and analysis will be performed to validate and/or refine the hypotheses raised in this paper.